Systems Science and Evidence-Informed Deliberation to Mitigate Dilemmas in Situations of Dual Agency at the Hospital Level; Comment on "Dual Agency in Hospitals: What Strategies Do Managers and Physicians Apply to Reconcile Dilemmas Between Clinical and Economic Considerations" - Leon Bijlmakers (Kerman University of Medical Sciences, 2022)
The article by Waitzberg et al on dual agency in hospitals reports on three strategies to mitigate dilemmas arising from conflicting clinical and economic considerations. This could be further explored by using systems science methods that allow in-depth analyses of (health) system dynamics, networks, and agent-based modelling, and that take into account local context, incentives and how institutions work. Future studies may also draw on the literature of multi-criteria decision-making and evidence-informed deliberative processes (EDPs) that are increasingly being used to optimise legitimate health benefit package design. Toolkits to assist hospital professionals in improving their decision-making need to be practical, with ample attention for the process of decision-making, including transparency, use of evidence, and opportunities for health professionals (and possibly others stakeholders) to contest or formally appeal against certain decisions.